2017
DOI: 10.1149/2.0691704jes
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Electron Transfer in Electrochemical System Based on Immobilized Gold Nanoparticles and Glucose Oxidase

Abstract: In this research some aspects of electron transfer (ET) in electrochemical system based on immobilized gold nanoparticles (AuNPs) and glucose oxidase (GOx) were investigated. It was shown that in the design of AuNPs and GOx modified graphite rod (GOx/AuNPs/GR) electrode the AuNPs are facilitating the electron transfer from GOx toward graphite rod electrode. It was determined that significant electrode currents and well-defined oxidation/reduction peaks were registered at potential sweep rate of 0.1 V s −1 . An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…[22][23]29] Yet, only a few studies focused on the effect of the shape and size of the NPs on DET. [31][32][33][39][40][41][42] For example, Willner and co-workers have shown that GOx can pump electrons directly to a confined metal particle and charge it. [39] We demonstrated [34] that the enzyme CDH catalyses the reduction of AuCl 4 À by DET from lactose in the presence of a catalytic metal surface, such as Pd, or AuNPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23]29] Yet, only a few studies focused on the effect of the shape and size of the NPs on DET. [31][32][33][39][40][41][42] For example, Willner and co-workers have shown that GOx can pump electrons directly to a confined metal particle and charge it. [39] We demonstrated [34] that the enzyme CDH catalyses the reduction of AuCl 4 À by DET from lactose in the presence of a catalytic metal surface, such as Pd, or AuNPs.…”
Section: Resultsmentioning
confidence: 99%
“…The conjugated GOx/Au NP showed reduced catalytic activity of the enzyme in solution; however enabled DET when immobilized onto an electrode. Furthermore, the efficiency of AuNPs for enzymatic activity of GOx was thoroughly studied by Ramanavicius and Ramanaviciene . They investigated the effect of the size of AuNPs and their enlargement in the oxidation of glucose catalyzed by GOx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies employed contact adsorption and/or electrochemical deposition to co-immobilize redox enzymes, molecular relays, and metallic nanoparticles, yielding effective bioelectrocatalysis. [17][18][19][20] Frequently used are also redox active mediators which are graed onto and/or constitute repetitive monomeric units in polymer hydrogels. [21][22][23] While the surface concentration of the relaying species in such assemblies is relatively high, these systems are prone to diffusional limitations of the enzymatic substrates and their products, hindering the charge transport and affecting the performance of the electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical sensors of the second generation are most commonly used in diabetes care (Freckmann et al, 2012;Hoenes et al, 2008). Thereby, electron-mediator components such as ferrocene derivatives, quinone compounds, and transition metal complexes ensure a stable electrochemical communication (Chen et al, 2013;Larik, Saeed, Fattah, Muqadar, & Channar, 2016;Mano et al, 2002;Márquez, Jiménez-Jorquera, Domínguez, & Muñoz-Berbel, 2017;Pilo et al, 2018;Pourasl et al, 2014;Ramanavicius, German, & Ramanaviciene, 2017;Zhu et al, 2012). Quinone diimines or hexacyanoferrates exhibit low unspecific interactions with blood components and therefore are commonly used in diabetes care (Vashist, Zheng, Al-Rubeaan, Luong, & Sheu, 2011).…”
Section: Introductionmentioning
confidence: 99%